2018
DOI: 10.3389/fncel.2018.00360
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Kcnmb2 in Dorsal CA1 of Offspring Mice Rescues Hippocampal Dysfunction Caused by a Methyl Donor-Rich Paternal Diet

Abstract: BK channels are known regulators of neuronal excitability, synaptic plasticity, and memory. Our previous study showed that a paternal methyl donor-rich diet reduced the expression of Kcnmb2, which encodes BK channel subunit beta 2, and caused memory deficits in offspring mice. To explore the underlying cellular mechanisms, we investigated the intrinsic and synaptic properties of CA1 pyramidal neurons of the F1 offspring mice whose fathers were fed with either a methyl donor-rich diet (MD) or regular control di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The KCNMB2 gene has been associated with suicidal ideation in US military veterans (Kimbrel et al , 2018) and may be related to depression, which is common in the elderly. Further, when KCNMB2 is overexpressed in the hippocampus of mice, it rescues memory deficits (Yu et al , 2018). More work is required to enable better understanding and identification of the molecular pathways involved in LATE.…”
Section: Introductionmentioning
confidence: 99%
“…The KCNMB2 gene has been associated with suicidal ideation in US military veterans (Kimbrel et al , 2018) and may be related to depression, which is common in the elderly. Further, when KCNMB2 is overexpressed in the hippocampus of mice, it rescues memory deficits (Yu et al , 2018). More work is required to enable better understanding and identification of the molecular pathways involved in LATE.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ activated K + channels: these channels use changes in Ca 2+ levels to regulate membrane conductance of K + (i.e., the entry and exit of the K ion) [ 76 ]. They are present in glial cells signaling [ 77 ] and also in the brain. A recent study using a mice-based animal model showed a correlation between the alteration of this gene and a reduced inhibitory synaptic transmission, as well as decreased neural intrinsic excitability in the mice [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they are involved in learning and memory (Raffaelli et al 2004;Lee and Cui 2010). The BK channel beta subunit 2, encoded by Kcnmb2, plays a role in the inactivation of BK channels (Yu et al 2018), and methyl donors have a transgenerational effect, specifically by altering Kcnmb2 methylation, a phenomenon that decreases its expression (Ryan et al 2018). These changes may be involved with our findings, where some neurotransmitters are increased.…”
Section: Discussionmentioning
confidence: 99%